Meetings for School-Based Decision Making - Babbage, Keen J. (Rowman & Littlefield Publishers, 1996)
Have you ever left a meeting feeling that nothing had actually been accomplished? This book provides you with the keys to running a successful and efficient meeting. Babbage begins with a section on how to prepare effectively for a meeting, methods for running a concise meeting, and finishes with how to implement the key decisions made during the meeting. He also includes a section on how to maintain everyone's involvement, cooperation, and interest throughout the meeting.